Identifikasi kromosom hasil cangkok anakan salak Sidempuan (Salacca sumatrana Becc.) di Kecamatan Angkola Barat - Meiliana Friska (Jurnal Pertanian Tropik, 2019)
Salak Sidimpuan (Salacca sumatrana Becc.) is one of the superior commodities in SouthTapanuli Regency. The availability of good quality zalacca varieties, high productivity,resistance to pests and diseases and tolerance to environmental stress are conditions that mustbe met in the era of agricultural industrialization. For this reason, it is necessary to assemblenew superior salacca cultivars to meet the evolving demands of consumers and to anticipatepotential cultivation constraints. Zalacca chromosome analysis is expected to be able toproduce information about the chromosome composition of these plants, which can then beuseful in supporting zalacca breeding. The aim of this study was to obtain the identity of theSalacca Sumatrana Becc. The plant-based on the morphological characteristics ofchromosomes (number, shape, and karyotype of chromosomes). This research was conductedat the Laboratory of Genetics, Faculty of Biology, University of North Sumatra, Medan inApril-May 2019. The results of this study indicate that Salak Sidempuan (Salacca sumatranaBecc.) have the number of chromosomes is 2n = 28, the shape of the chromosome and thekaryotype formula was 2n = 9m + 5 sm (9 metacentric chromosomes and 5 submetacentricchromosomes)